2012
DOI: 10.3138/ptc.2011-31bh
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Exercises on Function in Older Adults with Osteoporosis or Osteopenia: A Systematic Review

Abstract: Purpose: To examine the effect of resistance exercises on self-reported physical function and activities of daily living (ADL) in older adults with osteoporosis or osteopenia. Methods: A search of available literature was conducted using PubMed, CINAHL, SPORTDiscus, PEDro, ProQuest Nursing and Allied Health Source, and Cochrane Controlled Trials Register. Studies were included if they involved (1) randomized controlled trials; (2) participants with osteoporosis or osteopenia; (3) resistance exercise as an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
0
33
0
2
Order By: Relevance
“…Despite the effects of resistance training on bone mass and metabolism, a systematic review on the effects of resistance exercises on function in older adults with osteoporosis or osteopenia, revealed that interventions using resistance training have a beneficial effect on the domains of physical function and activities of daily life (19).…”
Section: Resistance Exercisesmentioning
confidence: 99%
“…Despite the effects of resistance training on bone mass and metabolism, a systematic review on the effects of resistance exercises on function in older adults with osteoporosis or osteopenia, revealed that interventions using resistance training have a beneficial effect on the domains of physical function and activities of daily life (19).…”
Section: Resistance Exercisesmentioning
confidence: 99%
“…The statistical results demonstrated that effect sizes ranged from 0.08 to 1.74, suggesting trivial to large treatment effects on self-reported function and ADL. 109 The results suggest that resistance training can have a beneficial impact in individuals with osteopenia or osteoporosis. The authors also suggest that more high-quality studies are needed to substantiate this conclusion further.…”
Section: Osteoporosis/vertebral Fracturesmentioning
confidence: 94%
“…The authors also suggest that more high-quality studies are needed to substantiate this conclusion further. 109 In another recent systematic review published in the Cochrane Database, the authors discussed the effects of exercise in individuals following osteoporotic vertebral fracture. 110 Seven trials, which consisted of 488 participants, were included in the fi nal analysis.…”
Section: Osteoporosis/vertebral Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…This review was based on a systematic search of published articles available through April 2015, and conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Virtual reality in elderly Ribeiro-Papa DC consensus. 24 In order to demonstrate the methodological quality of the studies, an article with a good level of evidence was considered to be one with a score equal to or higher than 6 according to the PEDro evaluation scale. This criterion was based on previous reports 18,20 which rated studies scoring 9-10 on the PEDro scale to be methodologically 'Excellent', 6-8 'Good', 4-5 'Fair' and below 4 'Poor'.…”
Section: ■ Methodsmentioning
confidence: 99%